2007
DOI: 10.1111/j.1365-2753.2006.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Are the outcomes of clinical pathways evidence‐based? A critical appraisal of clinical pathway evaluation research

Abstract: Readers should be cautious when interpreting the results of clinical pathway evaluation studies because of the confounding factors and sources of contamination affecting the evidence-based validity of the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 121 publications
0
37
0
Order By: Relevance
“…44 Retrospective case-control studies should not report the favorable experiences alone. An appropriate number of patients should be recruited to obtain a sufficient statistical power.…”
Section: Methodsmentioning
confidence: 96%
“…44 Retrospective case-control studies should not report the favorable experiences alone. An appropriate number of patients should be recruited to obtain a sufficient statistical power.…”
Section: Methodsmentioning
confidence: 96%
“…Other surveys from nursing institutions have described the use of clinical pathways, but no data was presented [25][26][27][28]. A systematic review by El Baz found that 91.3% of all studies on clinical pathways were retrospective, 59% adopted parametric statistical test, and overall 67% were classified as of low quality [17]. In the current study, we calculated detailed costs based on the used resources.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies are available, but are restricted to a single procedure, and cost analyses are mainly based on the length of hospital stay [6][7][8][9][10][11][12][13][14][15] (see Table 4). Most studies come from the US [16] and two thirds of studies on clinical pathways were classified as of low quality [17]. Notably, the issue of safety related to preset simplified flow sheets has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…CPW are multidisciplinary care plans that outline the sequence and timing of actions necessary for achieving expected patient outcomes and organizational goals regarding quality, costs, patient satisfaction and efficiency (El Baz et al, 2007). The aim of CPW is to link evidence to practice for specific health conditions (Rotter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%